Megye vagy régió a közigazgatási középszinten? a közigazgatási középszint fejlődésének rövid története 2000-ig - Deák, István (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The biggest dilemma of the Hungarian public administration, state administration nowadays is the future of the medium level administration. There are fierce debates in scientific and political circles about whether the county strengthened in its competencies should fill this position or the region functionning not always satisfactorily in the field of the territorial development. The picture is compleated by the theory of the „big county system" reappearing from time to time in scientific literature. The European spatial development and the appareance of the „city regions" lead to different solutions and development strategies in the member states of the EU. In Hungary, there has no step forward yet. The competencies, tasks of the „small regions" need to be clarified, only ad-hoc solutions were born depending on the political circumstancies without any conceptions in the long run.